AN IMAGINARY LAUGHTER: THE PORTRAYAL OF POLITICAL CARTOONS IN INDONESIAN MAGAZINE COVERS - Nugraha, Danang Satria (Universitas PGRI Sumatera Barat, 2024)
This study employs critical discourse analysis to examine how political cartoons are portrayed on Indonesian magazine covers. The study aims to explore how political cartoons construct and reinforce dominant ideologies, satirize political figures, and engage with societal issues. Using a qualitative approach, the study examines visual and textual elements in selected magazine covers, specifically Tempo. The study scrutinizes humor, symbolism, and caricature as rhetorical devices to convey political messages and critique power structures. It also investigates how cartoons use the synergy between image and text to shape public opinion and influence political discourse. The study’s findings reveal how political cartoons on magazine covers serve as a platform for dissent, challenging dominant narratives and providing alternative perspectives. Admittedly, the analysis uncovers the strategies used by cartoonists to navigate the boundaries of freedom of expression in a politically charged environment. This study offers valuable insights into the visual representation of political cartoons on Indonesian magazine covers, contributing to critical discourse analysis. It highlights the potential of cartoons as tools for social critique and democratic engagement, providing a deeper understanding of the role of humor and satire in political communication.